Meningkatkan Kemampuan Kecerdasan Visual melalui Aplikasi Paint di RA Al Muhajirin Kota Cimahi - Tati Hayati; Mimik Kurniawati; Ramdhan Witarsa (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
The purpose of research in this article is to find out how the activities of early childhood in improving the ability of visual intelligence through paint application in RA Al Muhajirin Kota Cimahi and to find out how much increase the ability of visual intelligence through paint applications. The research problem is how paint application done to visual intelligence of early child in RA Al Muhajirin Kota Cimahi. The research method used is Classroom Action Research method. Subjects in this study were all children early age of 30 children. The instruments used are observation guidelines, interviews, and documentation. Data analysis techniques used descriptive qualitative. Data analysis uses data reduction, data model, and conclusion. The results showed an increase in the underdeveloped category of 10 children (30%) to 1 child (3,6%), the category began to grow as many as 14 children (49,9%) to 5 children (17,8%), in the category developed as expected by 3 children (12,3%) to 6 children (21,4%), and in very good developing category as many as 3 children (9,7%) to 16 children (57,2%). It can be concluded that paint application can improve the ability of visual intelligence at early childhood in RA Al Muhajirin Kota Cimahi.